Efficacy of core stabilization program and conventional exercises in low back pain - Kumar, Arvind; Gupta, Vivek; Khan, Mansoor A.; Srivastava, Harshika (International Journal Of Community Medicine And Public Health, 2023)
Background: Patients experiencing low back pain (LBP) often benefit from therapeutic exercise. These exercises can retrain trunk muscles and improve spinal stability and sensory integration. Consequently, we aimed to compare the efficacy of a core stabilization program and conventional exercises in low back pain. Methods: This prospective, comparative study comprised 192 subjects aged 20-60 with nonspecific chronic low back pain (NSLBP). Core stabilization or usual physical therapy activities were randomly assigned to groups C or R. Both treatment groups received TENS and ultrasound therapy. Pretreatment, second, fourth, and sixth-week post-treatment outcomes were documented using a visual analogue scale (VAS). Results: Both groups were female-dominated. Height, weight, and BMI were comparable. At baseline, group C had a mean VAS score (5.69±1.80), while group R had (5.52±1.42). P value 0.4684 indicates no significant difference between exercise groups. At the final assessment, group C had a considerably (p<0.0001*) lower mean VAS score (2.96±0.39) than group R (3.89±0.98). Group C had a substantially higher mean VAS score change from baseline to the final evaluation (-2.73±0.51) than group R (-1.18±0.79). Conclusions: Core stabilization exercise is more effective than routine physical therapy exercise in terms of greater reduction in pain in chronic NSLBP.